[Strategic] Financial school management in Kurdistan region of Iraq - Kameran Noori Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
Strategic financial management ability, as one of the key leverage and key drivers of development, is a subject that has always been endorsed by experts and executives; however, it has been long neglected in the domain of education. Considering the importance of this issue in the area of education, this study aimed at investigating the school headmasters’ opinions towards this type of management and its implementation in the schools of the Kurdistan region of Iraq. In this respect, 12 high school principals from this context were selected as the participants of this study. The interview was used as the research instrument in this qualitative study. The findings which are elaborated in the results section revealed that the education system had acted very poorly in developing and improving the financial management in Kurdistan, and must try to provide better and appropriate training for the school headmasters and increase the school funding to help school principals remove the problems and difficulties they face in this regard.